دور التكوين الذاتي في الاداء الوظيفي عند الاطباء - بوخاتم, غزلان (كلية العلوم الإجتماعية لجامعة مستغانم, 2024)
تناولت الدراسة موضوع التكوين الذاتي وأهميته في أداء العنصر البشري في القطاع الصحي دراسة ميدانية في المستشفى الجامعي مستغانم وتهدف هذه الدراسة إلى توضيح الأهمية ودورالتكوين الذاتي لأداء العنصر البشري في المؤسسات الاستشفائية في الآونة الأخيرة خاصة مع للتطو رالعلمي والتكنولوجي في المجال الصحي و إمكانية الاستفادة من التكوين الذاتي عن بعد إضافة الى التكوين الحضوري. ونقاط اختلاف التكوين الذاتي عن التكوين الرسمي المقدم من طرف قطاع الصحة العمومية. وقد استخدمت المنهج الكيفي للقيام بهذاالبحث مع عينة متكونة من 15طبيب عاملين بالمستشف ىالجامعي لمستغانم .وقد استخدمت المقابلة: • تختلف إستراتيجية التكوين الرسمي عن إستراتيجية التكوين الذاتي من حيث (الزمن، المكان، طرقها، أنواعها). • التكوين الذاتي له دور فعال في تطوير مهارات الأطباء الشخصية والمهنية. • أصبح التكوين الذاتي ضرورة حتمية وهذا سبب توجه الأطباء لهذا النوع من التكوين • اختلاف في تنظيم للدوارات التكوينية وبرامجها حسب نوع التكوين والاحتياجاتالتكوينيةللعنصر البشري • اعتبار التكوين الذاتي أحد العمليات التي تعتبر تحدياً من طرف الأفراد رغم المشاكل التي تواجههم في بيئة العمل خاصة المرأة معظم الأطباء لهم الرغبة في التكوين الذاتي رغم الصعوبات والمعوقات (الوقت، المسؤولية، التنقل، التكاليف، العمل
دراسة ميدانية في المستشفى الجامعي
The study addressed the topic of self-development and its impact on the performance of human resources in the healthcare sector, through a field study conducted at Mostaganem University Hospital. The aim of this study was to clarify the importance and role of self-development in the performance of human resources in healthcare institutions, especially given recent scientific and technological advancements in the field. The qualitative method was utilized, with a sample of 15 participants interviewed through semi-structured interviews, including only doctors from Mostaganem University Hospital. The study arrived at the Followingconclusions: • Formal training strategies differ from self-development strategies in terms of timing, location, methods, and types. • Self-development plays an active role in developing personal and professional skills of doctors. • Self-development has become a necessity, leading doctors to prioritize this type of training. • Variations exist in the organization of training rotations and programs based on the type of training and the training needs of human resources. • Self-development is considered a challenging process by individuals, especially women, despite facing workplace issues. • Most doctors express a desire for self-development despite difficulties and obstacles (such as time constraints, responsibilities, mobility, costs, and workload) in order to enhance their capabilities and acquire new skills in the healthcare sector.
Keywords: self-development .the performance of human resources; التكوين الذاتي. القطاع الصحي